1995
DOI: 10.1111/j.1570-7458.1995.tb01930.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing codling moth larval response to α‐farnesene

Abstract: Behavioral responses of newly‐emerged codling moth (Cydia pomonella L.) larvae to α‐farnesene were compared for a laboratory‐reared strain (‘lab’, 160 generations inbred) and a recently collected strain (‘wild’, 3 generations). Video recordings of single larvae placed 20 mm from Bond papers releasing a range of seven α‐farnesene concentrations were scored for head turning, head lifting, head direction, and movement across a Petri dish. The laboratory strain was significantly less successful at finding the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…The two sesquiterpene isomers (E,E)-a-farnesene and (Z,E)-a-farnesene have a similar behavioural effect on mated females of the codling moth Cydia pomonella, with low dosages being attractive and high dosages repellent (Hern and Dorn 1999), emphasizing the importance of emitted amounts. (E,E)-a-Farnesene also stimulates oviposition and larval movement of the codling moth (Wearing and Hutchins 1973;Bradley and Suckling 1995;Landolt et al 2000). The sesquiterpene b-caryophyllene attracted codling moth females at a dosage measured in the headspace of the apple cultivar 'Golden Delicious' under field conditions .…”
Section: Discussionmentioning
confidence: 93%
“…The two sesquiterpene isomers (E,E)-a-farnesene and (Z,E)-a-farnesene have a similar behavioural effect on mated females of the codling moth Cydia pomonella, with low dosages being attractive and high dosages repellent (Hern and Dorn 1999), emphasizing the importance of emitted amounts. (E,E)-a-Farnesene also stimulates oviposition and larval movement of the codling moth (Wearing and Hutchins 1973;Bradley and Suckling 1995;Landolt et al 2000). The sesquiterpene b-caryophyllene attracted codling moth females at a dosage measured in the headspace of the apple cultivar 'Golden Delicious' under field conditions .…”
Section: Discussionmentioning
confidence: 93%
“…The adaptive significance of an increase in farnesene is difficult to interpret. On one hand, farnesene is an attractant to a number of herbivorous insects; this compound is among several in a volatile blend that elicits oviposition by European corn borer moths (Ostrinia nubilalis) (Binder et al 1995) and larval locomotory and orientation behavior in neonate codling moth caterpillars (Cydia pomonella) (Bradley & Suckling 1995). Thus, an elevation in its production could lead to greater damage.…”
Section: Discussionmentioning
confidence: 99%
“…Orientation of larval stages toward hostplant or prey odors have been shown in Lepidoptera, (Elasmopalpus lignosella, Huang and Mack 2002;Epiphyas postvittana, Suckling and Ioriatti 1996;Helicoverpa armigera Singh and Mullick 2002;Rembold et al 1989; Spodoptera littoralis, Khalifa et al 1973), Coleoptera (Cassida denticollis, Müller and Hilker 2000;Leptinotarsa decemlineata, Chin 1950;Dickens 2002; Cassida denticollis, Coccinella septempunctata, Stubbs 1980; Ctenicera destructor, Doane et al 1975; Diabrotica virgifera virgifera, Bernklau and Bjostad 1998a,b;Hippodamia convergens, Jamal and Brown 2001;Orthosoma brunneum, Paim and Beckel 1963) and Diptera (Drosophila melanogaster, Oppliger et al 2000; Delia antiqua, Mochizuki et al 1989; Psila rosae, Coaker 1977, 1979). Other behaviors including arrest and changes in speed or straightness of travel have also been observed, in addition to or in the absence of orientation behavior (Hughes et al 2003;Hunter 1978;Stubbs 1980;Jamal and Brown 2001;Bradley and Suckling 1995;Jones and Coaker 1977). In most of these studies, multiple behavioral mechanisms may contribute to the observed response.…”
Section: Introductionmentioning
confidence: 91%